Outsourcing How to Implement It Successfully - Krzysztof MURAWSKI; Monika MURAWSKA (Communications of International Proceedings, 2021)
The subject of the study is a quantitative and qualitative analysis of processes, taking into account the outsourcing strategy. The publication justifies the need and purpose of performing analysis on data held by organizations and discusses a selection of two data analysis methods that are commonly used in management science: quantitative analysis and qualitative analysis. The study shows that the use of outsourcing supported by quantitative and qualitative analysis may be an effective tool for optimizing the organization's processes, with particular emphasis on the main (key) processes of the organization and management processes. The example shows the benefits of quantitative and qualitative analysis of the processes and the prudent implementation of outsourcing in the organization.
Keywords: Quantitative and qualitative analysis; Organization; Processes; Outsourcing strategy